The Evolution of Human Resource Management in the Generation Z Era - Aryani, Dwi Nita (Journal of Economics, Management, Accounting and Computer Applications, 2025)
Generation Z, born between the mid-1990s and the early 2012s, a generation to have grown up in a digital, technology-driven world who tech-savviness, social consciousness, and desire for instant gratification. As the workforce, Human Resources Management (HRM) practices need to evolve to effectively engage and manage them. The aim of this study is to explore the implications of Generation Z on HRM practices. This study used a review of literature on Generation Z characteristics, preferences, and HRM practices. The research draws upon studies, articles, and reports related to HRM and Generation Z to analyze challenges and opportunities faced by HRM in managing this generation as employee. The results reveal that Generation Z employees value work-life balance, flexibility, and professional development opportunities. They prefer instant feedback, meaningful work, and a strong company culture. HRM practices need to adapt to meet these preferences by implementing flexible work arrangements, providing continuous feedback, and offering development opportunities. The Generation Z workforce presents both challenges and opportunities for HRM practices. By understanding their preferences and characteristics, organizations can tailor their HRM strategies to effectively engage and manage them. Adapting HRM practices is crucial for organizations to attract, retain, develop talent on digital in the future.